2008
DOI: 10.1364/oe.16.014004
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic all-PM femtosecond Yb-fiber laser stabilized with a narrow-band fiber Bragg grating and pulse-compressed in a hollow-core photonic crystal fiber

Abstract: We report on an environmentally stable self-starting monolithic (i.e. without any free-space coupling) all-polarization-maintaining (PM) femtosecond Yb-fiber laser, stabilized against Q-switching by a narrow-band fiber Bragg grating and modelocked using a semiconductor saturable absorber mirror. The laser output is compressed in a spliced-on hollow-core PM photonic crystal fiber, thus providing direct end-of-the-fiber delivery of pulses of around 370 fs duration and 4 nJ energy with high mode quality. Tuning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 8 publications
2
39
0
Order By: Relevance
“…However, its spectral bandwidth is now slightly larger and reaches 10 nm at FWHM. This low Kerr nonlinearity of the HC-PCF is in accordance with our earlier observations [2]. However, we note here that at the pulse energies reaching several nJ, and the pulse durations of only few hundred fs, as in this work, the Kerr nonlinearity of HC-PCF already becomes observable.…”
Section: Design and Performance Of The Lasersupporting
confidence: 93%
See 1 more Smart Citation
“…However, its spectral bandwidth is now slightly larger and reaches 10 nm at FWHM. This low Kerr nonlinearity of the HC-PCF is in accordance with our earlier observations [2]. However, we note here that at the pulse energies reaching several nJ, and the pulse durations of only few hundred fs, as in this work, the Kerr nonlinearity of HC-PCF already becomes observable.…”
Section: Design and Performance Of The Lasersupporting
confidence: 93%
“…On the other hand, lasers based on semiconductor saturable absorbers (SESAMs) can easily be made fully monolithic, and also have excellent self-starting properties, but in this case stabilization against detrimental Q-switching behavior requires a separate optical limiting mechanism. Our recent work demonstrated that fiber Bragg gratings can be used as an efficient stabilizing element, but at the price of reducing the pulse bandwidth to the sub-nm level, which results in a few picoseconds -long bandwidth-limited pulses [2,3]. A monolithic oscillator with a higher bandwidth and transform-limited output would be highly desirable because it would allow the use of either chirped-pulse [4] or parabolic [5] amplification to generate high-power ps pulses suitable for dispersive recompression.…”
Section: Introductionmentioning
confidence: 99%
“…1, consists of a modelocked linear cavity oscillator, a pre-amplifier, a power amplifier, and a spliced-on HC-PCF, which are separated by fiber optic isolators. Using such a spliced-on HC-PCF the output laser pulse can be compressed down to femtosecond duration with low loss and a high degree of polarization stability [4].…”
Section: Laser Design and Performancementioning
confidence: 99%
“…all-in-fiber, lasers with direct fiber-end fs pulse delivery were demonstrated so far (see e.g. [1], [2]). Here, the challenge lies in managing the dispersion both in and outside of the laser cavity without relying on mechanically unstable bulk-optics elements, such as grating pairs.…”
Section: Introductionmentioning
confidence: 99%